Efficacy and safety of CT-guided high-dose-rate interstitial brachytherapy in primary and secondary malignancies of the pancreas. Issue 112 (March 2019) - Omari, Jazan; Heinze, Constanze; Wilck, Antje; Hass, Peter; Seidensticker, Max; Seidensticker, Ricarda; Mohnike, Konrad; Ricke, Jens; Pech, Maciej; Powerski, Maciej
Abstract: Purpose: To evaluate efficacy and safety of CT-guided iBT in patients with primary and secondary malignancies of the pancreas. Material and methods: 13 patients with 13 lesions of the pancreatic corpus and tail were included: 8 secondary malignancies (metastatic lesions = ML) and 5 primary malignancies, including 3 primary tumors (PT) and 2 isolated locoregional recurrences (ILR) after surgical resection were treated with image-guided iBT using a 192iridium source (single fraction irradiation). Every 3 months after treatment clinical and imaging follow-up were conducted to evaluate efficacy. Peri- and postinterventional complications were assessed descriptively. Results: The median diameter of the gross tumor volume (GTV) was 3 cm (range 1–6.5 cm), treated with a median D100 (minimal enclosing tumor dose) of 15.3 Gy (range 9.2–25.4 Gy). Local tumor control (LTC) was 92.3% within a median follow-up period of 6.7 months (range 3.2–55.7 months). Cumulative median progression free survival (PFS) was 6.2 months (range 2.8–25.7 months; PFS of primary and secondary malignancies was 5.8 and 6.2 months, respectively). Cumulative median over all survival (OS) after iBT was 16.2 months (range 3.3–55.7 months; OS of primary and secondary malignancies was 7.4 months and 45.6 months, respectively). 1 patient developed mild acute pancreatits post iBT, spontanously resolved within 1 week. No severe adverse events (grade 3+) were recorded. Conclusion: Image-guided iBT is a safe and particularly effective treatment in patients with primary and secondary malignancies of the pancreas and might provide a well-tolerated additional therapeutic option in the multidisciplinary management of selected patients.